SOCIOLOGICAL CONDITION AND THE SETTING OF A STUDY IN SCARLET NOVEL - Wiruma Titian Adi (LPPM Universitas Bina Sarana Informatika, 2015)
Literature and society are relating each other. A literary work, such as novel, emerges from society and social condition. A Study in Scarlet is a famous novel about detective story. Its author’s life surely has an important role to this novel. In this thesis, the writer analyzes social condition of Conan Doyle. This analysis takes the data from novel A Study in Scarlet written by Conan Doyle. The supported theories collected through library and internet research. The writer uses descriptive qualitative method in analyzing this novel. Result of this analysis are first, sociological background of Conan Doyle are; a 28 years old man, live in London, study of medicine, live good in the middle class of economic and work as a surgeon and writer. Second, Conan Doyle’s reason in writing this novel are for beauty, foraging and imitate other’s behavior. Third, Conan Doyle’s social condition relates to the setting of this novel. Setting of place mostly in London, setting of time commonly in war time and setting of social concerns with war condition. Keywords: Character, Novel, Sociological Background